SIMULATION OF SHOCKS AND VIBRATIONS ON AVIATION SIMULATORS - Кабанячий, В. В.; Сотніков, Д. О. (Proceedings of National Aviation University (archive), 2021)
Methods of simulation on aviation simulators are given the most important shocks and vibrations of aircraft during movement at critical angles of attack, on the ground, the deviation of interceptors from the nose strut of the chassis and engines.